Caveolin-1: Functional Insights into Its Role in Muscarine- and Serotonin-Induced Smooth Muscle Constriction in Murine Airways - Keshavarz, Maryam; Schwarz, Heike; Hartmann, Petra; Wiegand, Silke; Skill, Melanie; Althaus, Mike; Kummer, Wolfgang; Krasteva-Christ, Gabriela (Frontiers in Physiology, 2017)
An increased bronchoconstrictor response is a hallmark in the progression of obstructive airway diseases. Acetylcholine and 5-hydroxytryptamine (5-HT, serotonin) are the major bronchoconstrictors. There are evidences that both cholinergic and serotonergic signaling in airway smooth muscle (ASM) involve caveolae. We hypothesized that caveolin-1 (cav-1), a structural protein of caveolae, plays an important regulatory role in ASM contraction. We analyzed airway constriction in different tracheal segments and extra- and intrapulmonary bronchi in cav-1 deficient (cav-1-/-) and wild-type mice using organ bath recordings and videomorphometry of methyl-beta-cyclodextrin (MCD) treated and non-treated precision-cut lung slices (PCLS). The presence of caveolae was investigated by electron microscopy. Receptor subtypes driving 5-HT-responses were studied by RT-PCR and videomorphometry after pharmacological inhibition with ketanserin. Cav-1 was present in tracheal epithelium and ASM. Muscarine induced a dose dependent contraction in all airway segments. A significantly higher Emax was observed in the caudal trachea. Although caveolae abundancy was largely reduced in cav-1-/- mice, muscarine-induced airway constriction was maintained, albeit at diminished potency in the middle trachea, in the caudal trachea and in the bronchus with without changes in the maximum efficacy. MCD-treatment of PLCS from cav-1-/- mice reduced cholinergic constriction by about 50%, indicating that cholesterol-rich plasma domains account for a substantial portion of the muscarine-induced bronchoconstriction. Notably, cav-1-deficiency fully abrogated 5-HT-induced constriction of extrapulmonary airways. In contrast, 5-HT-induced bronchoconstriction was fully maintained in cav-1-deficient intrapulmonary bronchi, but desensitization upon repetitive stimulation was enhanced. RT -PCR analysis revealed 5-HT1B, 5-HT2A, 5-HT6 and 5-HT7 receptors as the most prevalent subtypes in the airways. The 5-HT-induced-constriction in PCLS could be antagonized by ketanserin, a 5-HT2A receptor inhibitor. In conclusion, the role of cav-1, caveolae, and cholesterol-rich plasma domains in regulation of airway tone are highly agonist-specific and dependent on airway level. Cav-1 is indispensable for serotonergic constriction of extrapulmonary airways and modulates cholinergic constriction of the trachea and main bronchus. Thus, cav-1/caveolae shall be considered in settings such as bronchial hyperreactivity in common airway diseases and might provide an opportunity for modulation of the constrictor response.